PELAKSANAAN FUNGSI PEMERINTAHAN DESA DALAM MENINGKATKAN KETAHANAN EKONOMI MASYARAKAT DESA TEBING TINGGI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2023 - Herlambang, Andrian; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Law No. 6 of 2014 article 26 paragraph (1) states that the village head is in charge of organizing village government, carrying out village development, fostering village communities, and empowering village communities. In carrying out the duties of the village head as in article 26 paragraph (1) the village head is authorized to foster and improve the village economy and integrate it in order to achieve a productive scale economy for the greatest possible prosperity of the village community, which is the basis of the Tebing Tinggi Village Government to increase the economic resilience of the people of Tebing Tinggi Village, Benai District, Kuantan Singingi Regency by carrying out the development function, services, and community empowerment. The purpose of this study is to find out how the function of the Tebing Tinggi village government is in increasing the economic resilience of the Tebing Tinggi village community and to find out the factors that hinder the Tebing Tinggi village government in increasing the economic resilience of the Tebing Tinggi village community, Benai District, Kuantan Singingi Regency. The research method used is a qualitative method. This type of research is descriptive research. The research location is in Tebing Tinggi Village, Benai District, Kuantan Singingi Regency. This type of research is descriptive research. The research location is in Tebing Tinggi Village, Benai District, Kuantan Singingi Regency. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. This study found that the Tebing Tinggi Village Government has carried out development, service, and empowerment functions in increasing the economic resilience of the Tebing Tinggi village community. In increasing the economic resilience of the community, the Tebing Tinggi Village government has experienced obstacles, namely the lack of community participation in the programs provided by the village government to increase the economic resilience of the Tebing Tinggi Village community. Keywords : Development, Service, Empowerment.